Kayuh Ria Enterprise / Razali Yaakob ... [et al.] - Yaakob, Razali; Nordin, Norazila; Ab Rashid, Rozita; Amat, Amizul; Nazri, Mohd Dolshaufi; Ab Rahman, Nor Razita (Faculty of Sports Science and Recreation, 2000)
It is based from ETR 300 (Entrepreneurship) subject in Universiti Teknologi Mara (UiTM) we are encourage to extend what we had learned in university. We also have to related the knowledge we learned in Sports Studies in a form of business. Even the business we start is a small business, but we have a vision that someday we going to extend this business into a bigger and successful business. We hope that our effort in the business will attract all the 'bumiputra' to get involve in the business. Even we know this kind of business have a lot of competitors but we confidence that we can be a successful entrepreneur with a hard effort and a will to success.